2012
DOI: 10.4161/isl.20477
|View full text |Cite
|
Sign up to set email alerts
|

Islet amyloid polypeptide in pancreatic islets from type 2 diabetic subjects

Abstract: Keywords: amyloid deposit, islet amyloid polypeptide, immunocytochemistry, pancreatic islets, type 2 diabetes to unfold disappearing water-soluble IAPP in secretary granules from dying β-cells to refold water-insoluble polymerized amyloid fibrils in transforming β-sheet conformation in IAPP-containing islet deposits 8,14-17 by immunocytochemical staining using different dilutions of rabbit antihuman IAPP antibody. Results Control islets.The mean islet cell numbers of extra-large, large and medium-sized islets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 45 publications
1
33
0
1
Order By: Relevance
“…The morphologic appearance of these intratumoral lymphatic vessels resembles that of immature tumor venous vessels observed in other tissues [16]. There were similarly irregular lymphatic vessels in peritumoral tissues in MTCs, which match well with the newly formed, entrapped lymphatic vessels in the advancing margins of the tumor, resembling that of immature tumor blood vessels observed in the advancing margins of colonic carcinomas [17]- [20].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The morphologic appearance of these intratumoral lymphatic vessels resembles that of immature tumor venous vessels observed in other tissues [16]. There were similarly irregular lymphatic vessels in peritumoral tissues in MTCs, which match well with the newly formed, entrapped lymphatic vessels in the advancing margins of the tumor, resembling that of immature tumor blood vessels observed in the advancing margins of colonic carcinomas [17]- [20].…”
Section: Discussionsupporting
confidence: 54%
“…For evaluating LYVE-1 and F-8 immunostaining, morphometric analysis was performed using a mounted 1 cm linear scale with 10 µm intervals in the 10X eye piece. The length and width of LYVE-1 positive lymphatic vessels and F-8 positive venous vessels were measured in µm at 10 × 10 = 100× magnification as reported previously [16]. Both lymphatic and venous vessels were measured in the ten 100× fields for peri-and intra-tumor lesions and for non-tumor lesions, the latter was >1 cm away from the MTCs.…”
Section: Methodsmentioning
confidence: 99%
“…IDE is the key enzyme responsible for the intracellular degradation of hIAPP (Zraika et al, ). Although the primary function of IDE in mammalian tissues has traditionally been thought to degrade insulin, a number of other proteins have been identified as substrates of IDE, such as proinsulin, IGF‐II, relaxin, glucagon, Aβ and hIAPP (Tomita, ). Radio‐labeled hIAPP covalently cross‐linked to IDE in cell‐free extracts and also a monoclonal antibody directed against IDE immunoprecipitated both insulin and hIAPP, confirming that IDE is the hIAPP‐degrading protease (Zraika et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The first report on amyloid deposits in pancreatic islets of a diabetic subject was made over one hundred years ago. It is predicted that >300 million individuals worldwide will be affected by 2,025 (Tomita, ). Extensive IAPP deposits are thought to contribute to pancreatic β cell dysfunction, either by direct cytotoxicity or by reducing β cell mass resulting in impaired insulin secretion (Haataja et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the possible genetic and epigenetic factors 14 , researches revealed that multiple mechanisms may be involved in the β-cell apoptosis process 15 , including cytokines 16 , higher workload maintaining normal glycemia 17 , endoplasmic reticulum stress (ERS) 18 , elevated free fatty acid levels 19 , and accumulation of amyloids in pancreatic islets 20 . Medications that can inhibit β-cell apoptosis obviously prevent further reduction of β-cell mass, and thus become the potential treatment for diabetes.…”
Section: A N U S C R I P Tmentioning
confidence: 99%